Code-Switching and Code-Mixing in the Chinese Version Lyrics of the XOXO Album by EXO - Propungsri, Plernpit; Masrur, Muhammad Farhan; Alim, Shalsabila Putri; Fitria, Noor Laily (International Journal of Chinese Interdisciplinary Studies, 2023)
Abstract: Language is essential for communication, while music is a form of expression for sharing emotions and psychological states. A song written or performed in Mandarin may have English linguistic features. Code-mixing is a phenomenon that is different from interference and is instead a way for bilingual speakers to communicate a speech act. Code-switching involves the deliberate use of different languages for specific purposes, often within the same conversation. This study aimed to identify the types of code- switching and code-mixing in the lyrics of the XOXO EXO-M (Chinese version) album and to determine their roles. A descriptive method with a qualitative approach was used to analyze the data, which were collected, sorted, recorded, and coded for analysis. The analysis revealed 52 instances of data, comprising 35 occurrences of code-mixing and 17 instances of code-switching in the lyrics of the album.